Perencanaan Pangkalan Pendaratan Ikan (PPI) Di Pelabuhan Majene Dengan Menerapkan Konsep Biophilic Design - Tajuddin, Irham; AS, Zulkarnain; Alfiah, Alfiah (The Department of Architecture, Faculty of Science and Technology, Alauddin Islamic University of Makassar, 2022)
The development of the fishing industry in Majene Regency, such as the increasing number of fishermen, the increasing number of Rumah Tangga Perikanan (RTP) catch, and the increase in fishery production are not proportional to the condition of the existing port facilities. The facilities at Majene Port are not utilized due to the damaged condition of the facilities and the poor arrangement of the area. This study aims to plan and design a Pangkalan Pendaratan Ikan (PPI) in Majene Port by applying the concept of Biophilic Design. The research method used is primary data collection by means of field surveys/observations and interviews, secondary data collection is carried out by collecting data on literature studies, journals or scientific works related to titles, books, reading materials related to titles, and other literature. Rxploratory data collection in the form of the results of primary data analysis and secondary data. The planning of the Pangkalan Pendaratan Ikan (PPI) at Majene Port is expected to empower fishermen and fishmonger, from providing more adequate fish landing base facilities and good area arrangement by using the biophilic concept to remove the community's bad perspective about the unpleasant odor at the fish landing base.